AN ANALYTICAL STUDY OF ARAVIND ADIGA’S THE WHITE TIGER - Mahal, Ramandeep; Markandeshwar, Maharishi (International Journal of Psychosocial Rehabilitation, 2020)
Aravind Adiga’s The White Tiger is the narrative of a man named Balram Halwai, his fall from moral values and his upward social movement through crime and corruption. The writer actually paints a contemptuous and demeaning picture of Indian society. He actually through this literary work addresses the malaise of social inequality in India. He brings across the social aspirations of an ambitious but impoverished youth and his struggle to move into the upper echelons of society without scruples. The feeling of exclusion by Balram who in his quest for affluence stoops down to levels where a crime like murder and robbery is a matter of routine. His training ground apparently is his being a confidant of his younger master Ashok in the corridors of power of the capital where he is used for paying bribes and coordinating. Adiga projects Indian society as a warped system and one of the main issue is the functioning of a defunct society where political patronage and monetary gain are deeply connected and define the playing ground of the corrupt affluent. The glaring issue is the way Balram ‘The White Tiger’ (an exception of his social class) is able to get away with murder and theft and is able to successfully start an enterprise pointing to the strange phenomenon of a dysfunctional civilization. The present assessment of this paper appropriately incorporates the social issues inside the novel.